The Influence of Mining on Sediment Geochemistry of the Waitekauri Catchment, Waihi, New Zealand - J G. Webster-Brown; K L. Brown (The Australasian Institute of Mining and Metallurgy, 2003)
The Waihi Region is host to many low sulphidation epithermal Au-Ag deposits. The Golden Cross mine located at the head of the Waitekauri River, eight kilometres NW of Waihi, was a gold mining operation that placed significant emphasis on environmental management. An assessment of the influence of this mining project on stream sediment geochemistry (Fe, Mn, As, Cu, Pb, Zn, Cr, Cd, Ni, Ag and Se) in the Waitekauri Catchment has been made. Effective waste management during the mine operation appears to have prevented contamination of stream sediment. Trace metal concentrations in the Waitekauri Catchment sediment have generally decreased since 1987, and are currently mainly below the ANZECC (2000) sediment quality guidelines. However, elevated As levels were recorded in the Upper Waitekauri River and Battery Stream, exceeding guideline values. Elevated levels of Cu, Pb, Zn and Cd were found in the Huanui Stream, a tributary of the lower Waitekauri River. This reflects the influence of past mining operations in the valley, as well as natural weathering of hydrothermally altered Coromandel Group andesite. At a number of sites, Mn concentrations also exceeded sediment quality guidelines, and this may be derived from the remediated Golden Cross mine site.